2020
DOI: 10.4337/9781788973533
|View full text |Cite
|
Sign up to set email alerts
|

Research Handbook on Start-Up Incubation Ecosystems

Abstract: The entrepreneurial-ecosystem concept has recently gained renewed attention among entrepreneurship scholars, yet research in the fields of regional studies and international entrepreneurship has stayed notably silent on the role that incubating environments can have in driving entrepreneurial activities in developing rapidly internationalising born-global (BG) firms.In this exploratory study, we seek to further the discussion on the role that the entrepreneurial ecosystem can have in the research on internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…A key point worth of further investigation is related to the role that ecosystems play in the long run to assist spinoffs in their development path in turbulent times (as during the Covid‐19). Previous research has shown that ecosystems play a key role in favoring the creation and successful development of spinoffs (Novotny et al, 2020). While for the case, we presented the time occurred between the idea and the development of the ABU product was limited and it did not allow ecosystems to reconfigure and boost the commercialization of the ABU, we realize that different situations could have emerged in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…A key point worth of further investigation is related to the role that ecosystems play in the long run to assist spinoffs in their development path in turbulent times (as during the Covid‐19). Previous research has shown that ecosystems play a key role in favoring the creation and successful development of spinoffs (Novotny et al, 2020). While for the case, we presented the time occurred between the idea and the development of the ABU product was limited and it did not allow ecosystems to reconfigure and boost the commercialization of the ABU, we realize that different situations could have emerged in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of an entrepreneurial ecosystem is used to describe how the variety of individuals, organizations and institutions influence entrepreneurial activity in a particular context (Novotny et al, 2018). There are three main components in this definition: entrepreneurial, ecosystem, and entrepreneurial activity (Stam & Spigel, 2017).…”
Section: Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…The concept has been adopted by the sciences of economics and management, where it appears in several related guises, such as innovation ecosystems, business ecosystems, and entrepreneurial ecosystems (Rinkinen, 2016). The notion of a start-up incubation ecosystem, defined as a system of interdependent actors and factors which supports the creation and successful development of start-ups (Novotny, Clausen, Rasmussen, & Wiklund, 2018), is most closely connected to the entrepreneurial ecosystems approach. Since entrepreneurial ecosystems are a "critical tool for creating resilient economies based on entrepreneurial innovation" (Spigel, 2017, p. 49), regional authorities are advised to build an underlying support policy for creating and strengthening these ecosystems in the interest of economic development.…”
Section: Introductionmentioning
confidence: 99%